A New Strategy for Large Dynamic Piezoelectric Responses in Lead‐Free Ferroelectrics: The Relaxor/Morphotropic Phase Boundary Crossover. (6th September 2020) - Zhang, Le; Wang, Haoyu; Wang, Dong; Guo, Mengyao; Lou, Xiaojie; Wang, Danyang
Abstract: One of the key problems in the existing lead‐free piezoelectrics lies in how to further boost their dynamic piezoelectric responses, i.e., electrostrain and dynamic piezoelectric constants, in an effective and facile manner, making them comparable to those of widely used lead‐based counterparts. In this work, a new strategy is developed to largely improve the dynamic piezoelectric properties of lead‐free ferroelectrics using phase field simulations by combining the relaxor/ferroelectric crossover rendering potentially reversible electrostrain and the morphotropic phase boundary (MPB) providing easy paths of ferroelectric polarization rotations. Following the guidance of simulation results, Mn‐doped (Bi0.5 Na0.5 )TiO3 –BaTiO3 lead‐free piezoelectric ceramics with relaxor/MPB crossover are synthesized. A large reversible electrostrain ( S max ) of 0.55% with a promising piezoelectric constant d 33 * ( S max / E max ) of 917 pm V –1 at the designed relaxor/MPB crossover is obtained, outperforming almost all practical lead‐free counterparts when taking both electrostrain and dynamic piezoelectric constants into consideration. The strategy of utilizing relaxor/MPB crossover provides a new route for enhancing the dynamic piezoelectric responses in lead‐free ferroelectric perovskites. Abstract : A new strategy named relaxor/morphotropic phase boundary crossover is developed theoretically and verified experimentally to enable significant enhancement of electrostrain and dynamic piezoelectric constants in lead‐free ferroelectrics.